2008
DOI: 10.4161/cc.7.9.5792
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolar phosphataseCdc14Bis dispensable for chromosome segregation and mitotic exit in human cells

Abstract: In yeast, the protein phosphatase Cdc14 promotes chromosome segregation, mitotic exit, and cytokinesis by reversing M-phase phosphorylations catalyzed by Cdk1. A key feature of Cdc14 regulation is its sequestration within the nucleolus, which restricts its access to potential substrates for much of the cell cycle. Mammals also possess a nucleolar Cdc14 homolog, termed Cdc14B, but its roles during mitosis and cell division remain speculative. Here we analyze Cdc14B's subcellular dynamics during mitosis and rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 37 publications
5
76
2
6
Order By: Relevance
“…Consistent with previous reports of hCDC14 KO cells (22,28), the hCDC14A PD cells were viable. Flow cytometry (FACS) comparisons with WT cells revealed no significant differences in the distribution of cell cycle phases in hCDC14A PD (Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous reports of hCDC14 KO cells (22,28), the hCDC14A PD cells were viable. Flow cytometry (FACS) comparisons with WT cells revealed no significant differences in the distribution of cell cycle phases in hCDC14A PD (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Unlike budding yeast CDC14, neither human hCDC14A nor hCDC14B are essential for either cell viability or mitotic exit (22,28). Rather, hCDC14A has functions outside cell cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a Cdc14B-knockout HCT116 derivative has been presented (Berdougo et al, 2008). The same factor was previously shown to be required for premature APC/C activation in doxorubicin-treated U2OS cells, by using an short interfering RNA-based knockdown approach (Bassermann et al, 2008).…”
Section: Premature Apc/c Activation After G-irradiationmentioning
confidence: 91%
“…While fission yeast and C. elegans also rely to some extent on Cdc14 homologues, 68-72 the majority of eukaryotes do not need Cdc14 for mitotic exit. 73,74 A systematic RNAi screen in Drosophila S2 cells revealed that several phosphatases are required to progress through and exit mitosis. 75 In Xenopus egg extracts PP1, PP2A and calcineurin have been shown to oppose the Cdk1 activity.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%